Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set: 75

Answer

$(G-F)(7)= 5$ $(G-F)(3)= -1$

Work Step by Step

RECALL: $(G - F)(x) = G(x) - F(x)$ Using the rule above gives: $(G - F)(7) = G(7) - F(7)$ and $(G- F)(3)=G(3)- F(3)$ The graph shows that: $F(7)=-1$; $F(3)=2$ $G(7)=4$; $G(3)=1$ Thus, using the values above give: $(G-F)(7)=G(7) - F(7)=4-(-1) = 4+1 = 5$ $(G-F)(3)=G(3) - F(3) = 1-2=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.